Impact of residual inflammation on myocardial recovery and cardiovascular outcome in Takotsubo patients. (18th November 2020) - Lachmet‐Thebaud, Lucie; Marchandot, Benjamin; Matsushita, Kensuke; Sato, Chisato; Dagrenat, Charlotte; Greciano, Stephane; De Poli, Fabien; Leddet, Pierre; Peillex, Marilou; Hess, Sébastien; Carmona, Adrien; Jimenez, Charline; et al.
Abstract: Aims: Recent insights have emphasized the importance of myocardial and systemic inflammation in Takotsubo syndrome (TTS). In a large registry of unselected patients, we sought to evaluate whether residual high inflammatory response (RHIR) could impact cardiovascular outcome after TTS. Methods and results: Patients with TTS were retrospectively included between 2008 and 2018 in three general hospitals. Three hundred eighty‐five patients with TTS were split into three subgroups, according to tertiles of C‐reactive protein (CRP) levels at discharge (CRP <5.2 mg/L, CRP range 5.2 to 19 mg/L, and CRP >19 mg/L). The primary endpoint was the impact of RHIR, defined as CRP >19 mg/L at discharge, on cardiac death or hospitalization for heart failure. Follow up was obtained in 382 patients (99%) after a median of 747 days. RHIR patients were more likely to have a history of cancer or a physical trigger. Left ventricular ejection fraction (LVEF) at admission and at discharge were comparable between groups. By contrast, RHIR was associated with lower LVEF at follow up (61.7% vs. 60.7% vs. 57.9%; P  = 0.004) and increased cardiac late mortality (0% vs. 0% vs. 10%; P  = 0.001). By multivariate Cox regression analysis, RHIR was an independent predictor of cardiac death or hospitalization for heart failure (hazard ratio: 1.87; 95% confidence interval: 1.08 to 3.25; P  = 0.025). Conclusions: Residual high inflammatory response was associated with impaired LVEF at follow up and was evidenced as an independent factor of cardiovascular events. All together, these findings underline RHIR patients as a high‐risk subgroup, to target in future clinical trials with specific therapies to attenuate RHIR.